Technological prospection of internet of things in the context of smart hospitals (Research, Society and Development, 2020)
Anchored in the internet of things (IoT) paradigm, Smart Hospitals have emerged as an innovative proposal for hospitals, where the functions of diagnosis, treatment, management and decision are integrated. In view of the great problems that hospitals around the world have faced, the need for an intelligent environment within the hospital context has been urgent, and the benefits brought by IoT for this sector are numerous. Understanding the importance of this theme, this work proposed to carry out a technological prospection study based on patents and scientific articles, in order to investigate technologies based on the IoT paradigm with application in hospital environments. Thus, searches were carried out on the Questel-Orbit databases, for patent documents, and Scopus, for scientific articles. Through patent and bibliometric analyzes it was possible to build a mapping of technologies and scientific research on IoT with application in hospitals, within the time frame from 2009 to 2020. The results pointed to an exponential growth of patent deposits and publications of articles on this topic. Technologies for digital information transmission devices, and measurement technologies for diagnostic purposes, were highlighted within the universe investigated. Information and communication technologies adapted for specific purposes were the ones that grew the most in this period. In addition, it was possible to observe China as a major producer of IoT technologies for hospitals, while India has gained prominence in terms of scientific research on this topic. The work provided an insight into the main trends of IoT for hospitals.